Improved Coulomb collision operator for kinetic ion transport with EMC3-EIRENE simulating Nitrogen seeding in medium density ITER L-mode scenario - D. Harting; D. Reiser; S. Rode; J. Romazanov; P. Börner; Y. Feng; H. Frerichs; A. Knieps (Nuclear Materials and Energy)
Previous simulations with the kinetic ion transport module of EMC3-EIRENE for Nitrogen seeding in a medium density ITER L-mode scenario showed that the currently simplified Coulomb collision model of EIRENE leads to a strongly overestimated confinement of the kinetic ions in the magnetic mirror regions. This simplified Coulomb collision model in EIRENE is based on an energy relaxation time only and is not changing the ratio of the parallel and perpendicular velocity components for the kinetic ions and thus does not include any scattering of the kinetic ions into the loss cone of the magnetic mirror. We have now implemented a new Coulomb collision operator in EIRENE, where the Coulomb collisions are described by a linear kinetic equation in Fokker-Planck form utilizing the Trubnikov-Rosenbluth potential functions, which includes scattering of the kinetic ions as well as friction with the background plasma. The Fokker-Planck equation is treated by an operator splitting scheme and is solved locally by a Monte-Carlo method. The choice of a small enough time step in the Monte-Carlo integration method is crucial and depends strongly on the local plasma background. Two methods to locally adapt the Monte-Carlo integration time step were implemented. One uses simply a fraction (∼10–4) of the local Spitzer slowing down time and the other applies an adaptive time step control with error estimation. It turns out that simulations using the adaptive time step control method are up to a factor 10 faster compared to the time step control using the Spitzer slowing down time. In this work we will present the details of this newly implemented Coulomb collision operator for kinetic ions in EMC3-EIRENE and the implementation of the adaptive time step algorithm. We applied this new Coulomb collision operator in a kinetic ion simulation with EMC3-EIRENE for Nitrogen seeding, where we puffed Nitrogen from the top of the machine in an attached medium density ITER L-mode scenario (nsep = 1×1019 m−3, Psep = 20 MW). This shows that the unphysical and exaggerated confinement of the kinetic ions in the magnetic mirror regions observed with the simplified Coulomb collision model in EIRENE is now resolved with the new Coulomb collision operator, which treats the scattering of the kinetic ions into the loss cone of the magnetic mirror correctly.